Effects of food quality on growth and biochemical composition of a calanoid copepod, Argyrodiaptomus furcatus, and its importance as a natural food source for larvae of two tropical fishes - Helena Sipaúba-Tavares, Lúcia [UNESP]; Adriana Bachion, Maria [UNESP]; Manoel de Souza Braga, Francisco [UNESP] (Springer Nature, 2001)
Growth, reproduction and biochemical composition were analyzed for the copepod Argyrodiaptomus furcatus fed on the alga Ankistrodesmus gracilis grown in different media. The ingestion of this copepod by larvae of two species of tropical fishes was also evaluated. The mean peak density of the copepod population was 1369 individuals 1-1 for all four diets used, and the highest was 1387 individuals 1-1 on diet ARV (algae + ration + vitamins). A small copepod, A. furcatus tends to have a short life span. The smallest females did not attain maturity in the shortest time on all diets used. Food quality may play a major role in the dynamics of the biochemical composition of this copepod. Argyrodiaptomus furcatus was a more important food item for larvae of tambaqui (Colossoma macropomum) than of pacu (Piaractus mesopotamicus). However, it made up a large part of the gut contents of larvae of both species.
Keywords: Biochemical composition; Calanoid copepods; Copepod culture; Growth; Natural food; Algae; Biochemistry; Fisheries; Growth kinetics; Nutrition; Vitamins; Food qualities; Biodiversity; biochemical composition; food quality; growth rate; zooplankton; algae; Ankistrodesmus; Ankistrodesmus gracilis; Calanoida; Colossoma macropomum; Colossoma marcopomum; Copepoda; Invertebrata; Piaractus; Piaractus mesopotamicus; Pisces